Paroxysmal nocturnal hemoglobinuria and vascular liver disease: Eculizumab therapy decreases mortality and thrombotic complications. Issue 4 (31st January 2022) - Plessier, Aurélie; Esposito‐Farèse, Marina; Baiges, Anna; Shukla, Akash; Pagan, Juan Carlos Garcia; De Raucourt, Emmanuelle; Ollivier‐Hourmand, Isabelle; Cervoni, Jean‐Paul; De Ledinghen, Victor; Tazi, Zoubida; Nousbaum, Jean‐Baptiste; Bun, René; et al.
Abstract: A total of 2%–10% of patients with vascular liver disease (VLD) have paroxysmal nocturnal hemoglobinuria (PNH). Eculizumab reduces complement‐mediated haemolytic activity in PNH. This study was aimed at assessing the impact of eculizumab on VLD outcome. Retrospective cohort of PNH patients, in Valdig registry, who had VLD diagnosed between 1997 and 2019 is considered. Eculizumab was the exposure of interest. Studied outcomes were death, venous thrombosis, bleeding, arterial ischemic event, infection, and liver‐related complications. We compared survival and new thrombotic events from PNH/VLD cohort to Envie2 non‐PNH cohort. Sixty‐two patients (33 women), median age 35 years (28–48) and median follow‐up VLD diagnosis 4.7 years (1.2–9.5), were included. Clone size was 80% (70–90), median hemoglobin concentration was 10.0 g/dl (8–11), and lactate dehydrogenase (LDH) was 736 IU (482–1744). Forty‐two patients (68%) had eculizumab; median exposure time was 40.1 [9.3–72.6] months. Mortality was significantly lower in exposed versus nonexposed period: 2.6 versus 8.7 per 100 (PY), incidence rate ratio (IRR) was 0.29, 95% CI (0.1–0.9), p  = .035. Thrombosis recurrence occurred less frequently during the exposure to eculizumab: 0.5 versus 2.8 per 100 PY, IRR 0.22 (0.07–0.64). Other secondary end points (i.e., bleeding, arterial ischemic lesions, infection, and liver complications) were less common during the exposure to eculizumab, although not reaching statistical significance. Six‐year thrombosis‐free survival was 70%, 95% CI [0.60–0.83] for PNH cohort and 83%, 95% CI [0.70–1.00] for non‐PNH Envie 2 patients, ( p  < .001). In conclusion, patients with PNH and VLD are at higher risk of recurrent thrombosis than non‐PNH patients. Eculizumab is significantly associated with a lower mortality and less thrombotic recurrence in patients with PNH and VLD.